Plan de marketing para agroindustria láctea de pequeños productores de Santo Domingo-Nutralac, del cantón Cayambe provincia de Pichincha - Albuja Arias, Jorge Marcelo (2014)
Nutralac is a center that produces and sells raw milk, cheese, mozzarella and yogurt, is located in Cayambe, Pichincha province; the organization represents small milk producers, so consider developing our thesis in order to provide a tool to help improve their sales. Determine acceptance, in this paper the analysis of micro and macro environment in which the organization SWOT was determined after defining the problem, which was solved by the application of research methods, tasting and taking surveys was conducted Nutralac of products and segment the market to be targeted. With the results of the research proposed, implemented several marketing strategies which allow them to enter through penetration by price, position your brand in the market and expand its distribution coverage.